2015
DOI: 10.1007/s13197-015-1719-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the heat-induced structural changes of alkaline phosphatase by molecular modeling, fluorescence spectroscopy and inactivation kinetics investigations

Abstract: The heat induced conformational changes of calf alkaline phosphatase (ALP) were analyzed using different methods, based on fluorescence spectroscopy, m o l e c u l a r m o d e l i n g a n d i n a c t i v a ti o n s t u d i e s . Experimental studies were conducted in buffer solution in the temperature range between 25 and 70°C. Molecular dynamic (MD) simulation provided details on thermally induced changes in ALP structure, highlighting that heating favored the hydrophobic exposure and important alteration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Other studies involving alkaline phosphate lipase have shown that conformational changes caused by thermal treatment C 2018 Institute of Food Technologists ® Vol. 18, 2019 r Comprehensive Reviews in Food Science and Food Safety 253 were the loss of helix and the exposure of hydrophobic regions, when temperature increased from 25 to 60°C (Dumitrașcu et al, 2015). This study indicated that the unfolding of this enzyme was promoted at temperature above 60°C and that the interaction of the catalytic residues with other residues was changed, with disappearance and reforming of hydrogen bonds at temperatures over 60°C.…”
Section: Influences Of Processing Conditions (Pressure and Temperaturmentioning
confidence: 70%
See 1 more Smart Citation
“…Other studies involving alkaline phosphate lipase have shown that conformational changes caused by thermal treatment C 2018 Institute of Food Technologists ® Vol. 18, 2019 r Comprehensive Reviews in Food Science and Food Safety 253 were the loss of helix and the exposure of hydrophobic regions, when temperature increased from 25 to 60°C (Dumitrașcu et al, 2015). This study indicated that the unfolding of this enzyme was promoted at temperature above 60°C and that the interaction of the catalytic residues with other residues was changed, with disappearance and reforming of hydrogen bonds at temperatures over 60°C.…”
Section: Influences Of Processing Conditions (Pressure and Temperaturmentioning
confidence: 70%
“…Simulations have shown that the exposure of hydrophobic core and the transition from an ordered to a disordered state are the common phenomena during the thermal denaturation of these proteins. Other studies involving alkaline phosphate lipase have shown that conformational changes caused by thermal treatment were the loss of helix and the exposure of hydrophobic regions, when temperature increased from 25 to 60 °C (Dumitrașcu et al., ). This study indicated that the unfolding of this enzyme was promoted at temperature above 60 °C and that the interaction of the catalytic residues with other residues was changed, with disappearance and reforming of hydrogen bonds at temperatures over 60 °C.…”
Section: Simulations To Evaluate the Dynamic Behaviors Of Componenmentioning
confidence: 99%
“…Also, it was observed that enzymatic activity remained stable after 2 hr of incubation at 65°C (Figure c). Alkaline phosphatases with thermal stability have been described before in microorganisms, plant seeds, and bovine samples (Dumitrascu et al, ; Mahesh, Neha, Rajesh, Somashekhar, & Puttiah, ; Vemuri, Sunkara, Arumalla, Nelapati, & Lakkoju, ; Fadiloğlu, Erkmen, & Sekeroğlu, ). We chose to perform all next experiments in pH 9.5 at 37°C.…”
Section: Resultsmentioning
confidence: 95%
“…where r RA is a reaction term considering the reduction of RA by thermal inactivation. The reaction is modeled as a first order kinetic, as described elsewhere (Jaeger et al, 2010;Dumitraşcu et al, 2015), thus…”
Section: Thermofluiddynamical Model Of the Pef Processmentioning
confidence: 99%